Effects of Mud Supply and Hydrodynamic Conditions on the Sedimentary Distribution of Estuaries: Insights from Sediment Dynamic Numerical Simulation - Qian Zhang; Mingming Tang; Shuangfang Lu; Xueping Liu; Sichen Xiong (Journal of Marine Science and Engineering, 2023)
Estuaries are important sediment facies in the fluvial-to-marine transition zone, are strongly controlled by dynamic interactions of tides, waves, and fluvial flows, and show various changes in depositional processes and sediment distribution. Deep investigations on the sediment dynamic processes of the sand component of estuaries have been conducted; however, the understanding of how mud supply affects estuaries’ sedimentary characteristics and morphology is still in vague. Herein, the effects of mud concentration, mud transport properties, fluvial discharge, and tidal amplitude on the sedimentary characteristics of an estuary were systematically analyzed using sedimentary dynamic numerical simulation. The results show that the mud concentration has significant effects on the morphology of tidal channels in estuaries, which become more braided with a lower mud concentration, and straighter, with reduced channel migration, with a higher mud concentration. The mud transport properties, namely, setting velocity, critical bed shear stress for sedimentation, and erosion, mostly affect the ratio between the length and width (RLW) of the sand bar; a sheet-like sand bar with a lower RLW value develops in the lower settling velocity, while there are obvious strip shaped bars with a high RLW value in the higher settling velocity case. Moreover, the effects of hydrodynamic conditions on sedimentary distribution were analyzed by changing the tidal amplitudes and fluvial discharges. The results show that a higher tidal amplitude is often accompanied by a stronger tidal energy, which induces a more obvious seaward progradation, while a higher fluvial discharge usually yields a higher deposition rate and yields a greater deposition thickness. From the above numerical simulations, the statistical characteristics of tidal bars and mud interlayers were further obtained, which show good agreement with modern sedimentary characteristics. This study suggests that sedimentary dynamic numerical simulation can provide insights into an efficient quantitative method for analyzing the effects of mud components on the sediment processes of estuaries.